Does clean energy contribute to economic growth? Evidence from Nigeria - Ibrahim Kabiru Maji (Energy Reports, 2015)
This paper examines the impact of clean energy on economic growth in Nigeria. Autoregressive distributed lag (ARDL) approach to cointegration was used to determine the existence of cointegration among the variables. The long run results suggest a significant negative relationship between two indicators of clean energy (alternative and nuclear energy and electric power consumption) and economic growth. The result further reveals a significant positive relationship between combustible renewables and waste and economic growth. Mixture of negative and positive relationships between clean energy indicators and economic growth was obtained in the short, although not significantly different from zero. We concluded that Nigeria has Potentials of clean energy to be reaped in near future.
Keywords: 330; Clean energy; Economic growth; Nigeria